Pengaruh Strategi Pembelajaran Genius Learning dan Gaya Belajar Terhadap Hasil Belajar Aqidah Akhlak Materi Menerapkan Akhlak Terpuji Pada Siswa Kelas Viii Mts Pab-4 Helvetia Medan - Sahyan (Hikmah, 2017)
This research aims to determine: (1) The difference in learning outcomes of students who are taught using learning strategies genius learning with expository, (2) Difference between the learning outcomes of students who have a kinesthetic learning style with students visual, (3) the interaction between the learning strategies and learning styles to learning outcomes. Implement strategies and learning outcomes measurement performed on the lessons Aqidah Akhlak apply finer material in class VIII MTs PAB-4 Helvetia Medan. The method used is the method of quasi experimental factorial 2x2. The results showed a significant difference in learning outcomes of students who are taught by the genius learnig learning strategies and expository. This is evident from the acquisition of p-value=0.000>0.05. There were no differences in learning outcomes of students with visual kinesthetic learning style. It looks acquisition p-value=0.119>0.05. There is no interaction learning strategies and learning styles on learning outcomes, it is seen from acquiring a p-value= 0:0 =0:05.